2008
DOI: 10.1016/j.bulsci.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dirichlet to Neumann operator on differential forms

Abstract: We define the Dirichlet to Neumann operator on exterior differential forms for a compact Riemannian manifold with boundary and prove that the real additive cohomology structure of the manifold is determined by the DN operator. In particular, an explicit formula is obtained which expresses Betti numbers of the manifold through the DN operator. We express also the Hilbert transform through the DN map. The Hilbert transform connects boundary traces of conjugate co-closed forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
100
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 7 publications
0
100
0
Order By: Relevance
“…The Euler characteristic in turn determines the topology of X in the latter case. The article [BSh08] generalises this result to higher dimensions. More precisely, the authors define a Dirichlet to Neumann operator on the space of differential forms of all degrees and express the Betti numbers of X in terms of this operator.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The Euler characteristic in turn determines the topology of X in the latter case. The article [BSh08] generalises this result to higher dimensions. More precisely, the authors define a Dirichlet to Neumann operator on the space of differential forms of all degrees and express the Betti numbers of X in terms of this operator.…”
Section: Introductionmentioning
confidence: 89%
“…The Dirichlet to Neumann operator of [BSh08] maps differential forms of degree i on ∂X to those of degree n−i−1, i.e., it does not preserve the natural graduation of the space of differential forms. Moreover, as substitution for the Dirichlet problem, the boundary value problem for harmonic forms u on X is chosen, with prescribed data t(u) = u 0 and t(d * u) = 0 on ∂X , where t(d * u) is the tangential component of d * u on the boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Now ( Ω, g ) and the (unknown) original (Ω, g) are two Riemannian manifolds with common boundary Γ, connected by the (unknown) diffeomorphism j := s −1 t * ; see (1.5). 7 These are metrics in which the real and imaginary parts of functions from A ( Ω) are harmonic. 6 Functions from A ( Ω) play the role of local complex coordinates.…”
mentioning
confidence: 99%
“…Without carrying out the full recovery scheme 1-4, we can use Λ to define some topological invariants of Ω: the Betti numbers and others; see [2], [7].…”
mentioning
confidence: 99%
“…The classical Dirichlet-to-Neumann map was generalized to an operator on differential forms independently by Joshi and Lionheart [JL05] and Belishev and Sharafutdinov [BS08]. Joshi and Lionheart called their operator Π and showed that the data (∂M, Π) determines the C ∞ -jet of the Riemannian metric at the boundary.…”
Section: Introductionmentioning
confidence: 99%